Patient Perceptions About Acne, Nutrition, and a Dietary Information Gap - Smollich, Martin; Tischner, Lea (Frontiers in Communication, 2022)
There is increasing evidence that certain dietary factors affect the course of acne vulgaris. The primary aim of this exploratory survey was to reveal patients’ perceptions of a possible link between acne and diet. Secondary, patients’ perceptions of the quality of nutritional communication, sources of dietary information, and a dietary information gap, have been investigated. An online survey is conducted on Instagram using a structured questionnaire in German. Data is analyzed quantitatively and qualitatively, and chi-square tests are performed. Results showed that most of the 1,040 participants believe that there is a connection between acne and diet (75%). However, due to a frequent lack of nutritional consultation by dermatologists (87%), participants’ nutritional information needs are not met. Therefore, they seek additional sources of information, mainly Instagram (63%), online forums (54%), and textbooks (46%). However, the participants feel that their nutritional interventions are unsuccessful and believe that an information gap exists. This study draws attention to the existence of an information gap regarding the topic of acne and nutrition. Adequate patient education on currently available data and its limitations is urgently needed to counteract patients’ long-held beliefs in diet and acne myths.